Telehealth through the pandemic at a safety net hospital: observations and next steps for cancer care delivery - Erin Thomas; Alice Kennedy; William Walsh; Michelle Carpentier; Hannah Adeyinka; Shyam Patel; Jonathan Gerber; Jan Cerny; Kriti Mittal (Frontiers Media S.A., 2023)
The COVID-19 pandemic revolutionized cancer care delivery leading to rapid adoption of digital technology for telehealth in the United States. In this study, we describe telehealth utilization trends across the three largest waves of the pandemic at a safety net academic center. We also provide a perspective on lessons learnt and our vision for cancer care delivery using digital technology in the near future. The integration of interpreter services within the video platform and its integration within the electronic medical record system is crucial for safety net institutes that service a diverse patient population. Pay-parity for telehealth, especially ongoing support for audio-only visits, will be critical in overcoming health disparities for patients without access to smartphone technology. Use of telehealth in clinical trials, widespread adoption of hospital at home programs, electronic consults for rapid access, and structured telehealth slots in clinic templates will be crucial in making cancer care more equitable and efficient.